Keefektifan Sistem ERP Dan Teknologi Terhadap PT Buyung Poetra Sembada Tbk Pada Tahun 2019-2020 - Dika Candra Laili; Hwihanus Hwihanus (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2022)
From this distribution, in 2011, the company opened a factory to process its rice in Subang for the first time with a production capacity of 86,000 tons/year. Due to the large amount of rice produced, the company opened its distribution center and warehouse in Surabaya, East Java in 2013. Beginning in 2014, sales boomed to reach IDR 500 billion. And it was from here that the company increased its production capacity, which was originally only 86,000 tons/year to 30 tons/hour and added grain processing machines. In 2016, the company achieved a sales turnover of up to IDR 1 trillion and launched a new brand called “HOKI”